2021
DOI: 10.1126/scisignal.abc9012
|View full text |Cite
|
Sign up to set email alerts
|

The dimeric form of CXCL12 binds to atypical chemokine receptor 1

Abstract: The pleiotropic chemokine CXCL12 is involved in diverse physiological and pathophysiological processes, including embryogenesis, hematopoiesis, leukocyte migration, and tumor metastasis. It is known to engage the classical receptor CXCR4 and the atypical receptor ACKR3. Differential receptor engagement can transduce distinct cellular signals and effects as well as alter the amount of free, extracellular chemokine. CXCR4 binds both monomeric and the more commonly found dimeric forms of CXCL12, whereas ACKR3 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 92 publications
(143 reference statements)
0
14
0
Order By: Relevance
“…17βHSD2 decreased potent androgen production by converting testosterone or dihydrotestosterone to each of their upstream precursors ( 40 ), which might provide new strategies for clinical management. On the other hand, chemokine signaling regulates tumor metastasis ( 41 ). CXCL12, a member of the chemokine family, and its receptor, CXCR4, are key mediators of PCa bone metastasis ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…17βHSD2 decreased potent androgen production by converting testosterone or dihydrotestosterone to each of their upstream precursors ( 40 ), which might provide new strategies for clinical management. On the other hand, chemokine signaling regulates tumor metastasis ( 41 ). CXCL12, a member of the chemokine family, and its receptor, CXCR4, are key mediators of PCa bone metastasis ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 was initially described to bind to the receptor CXCR4; however, CXCL12 also binds to the atypical chemokine receptor 3 (ACKR3) (also known as CXCR7) ( 18 ). Dimeric CXCL12 also binds to ACKR1 in Madin-Darby canine kidney cells and erythrocytes ( 19 ). CXCL12 is constitutively expressed by many endothelial cell types and promotes the arrest and TEM of leukocytes under physiological shear flow by binding to CXCR4.…”
Section: Resultsmentioning
confidence: 99%
“…44 Although it was previously reported that CXCL12 is not a ligand for ACKR1, 45 a new study shows that ACKR1 binds preferentially to the dimeric form of CXCL12. 46 Understanding the extent to which CXCR4, ACKR3, and ACKR1 mediate the biological effects exerted by CXCL12(3−68) and its dimeric isoform will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the atypical chemokine receptor 1 (ACKR1) was not included in the PRESTO-Tango screen, and this receptor was recently found to be expressed at high levels in the nucleated erythroid cells that make up the red pulp of the bone marrow . Although it was previously reported that CXCL12 is not a ligand for ACKR1, a new study shows that ACKR1 binds preferentially to the dimeric form of CXCL12 . Understanding the extent to which CXCR4, ACKR3, and ACKR1 mediate the biological effects exerted by CXCL12(3–68) and its dimeric isoform will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%